Ylide‐Stabilized Phosphenium Cations: Impact of the Substitution Pattern on the Coordination Chemistry. Issue 8 (5th January 2022) - Stalder, Tobias; Krischer, Felix; Steinert, Henning; Neigenfind, Philipp; Gessner, Viktoria H.
Abstract: Although N‐heterocyclic phosphenium (NHP) cations have received considerable research interest due to their application in organocatalysis, including asymmetric synthesis, phosphenium cations with other substitution patterns have hardly been explored. Herein, the preparation of a series of ylide‐substituted cations of type [YPR] + (with Y=Ph3 PC(Ph), R=Ph, Cy or Y) and their structural and coordination properties are reported. Although the diylide‐substituted cation forms spontaneous from the chlorophosphine precursor, the monoylidylphosphenium ions required the addition of a halide‐abstraction reagent. The molecular structures of the cations reflected the different degrees of electron donation from the ylide to the phosphorus center depending on the second substituent. Molecular orbital analysis confirmed the stronger donor properties of the ylide systems compared to NHPs with the mono‐ylide substituted cations featuring a more pronounced electrophilicity. This was mirrored by the reaction of the cations towards gold chloride, in which only the diylide‐substituted cation [Y2 P] + formed the expected LAuCl] + complex, while the monoylide‐substituted compounds reacted to the chlorophosphine ligands by transfer of the chloride from gold to the phosphorus center. These results demonstrate the tunability of ylide‐functionalized phosphorus cations, which should allow for further applications in coordination chemistry in the future. Abstract : Switching selectivity : The isolation and coordination chemistry of a series of ylide‐substituted phosphenium cations is reported. The monoylidyl cations exhibit a distinctly higher reactivity and electrophilicity, thus yielding a chlorophosphine gold cation via chloride shift from gold to phosphorus. In contrast, the diylidyl cation formed the phosphenium AuCl complex, demonstrating the tunability of the phosphenium cation reactivity.